Influencing Mechanism of Justice Sensitivity on Knowledge Hiding in the Chinese Context - Jin-song, Zhang; Hua, Huang; Dan-yang, Ruan; Ya-nan, Jin (Frontiers in Psychology, 2022)
Good knowledge management is important for enterprises to maintain competitive advantage; however, the knowledge hiding behavior may hinder this process. Based on the conservation of resources and psychological ownership theories, using a chain intermediary model, this study investigates the effect of justice sensitivity on knowledge hiding through perceived time pressure and territoriality, and further tests the moderating role of territoriality. For the study, we collected 436 questionnaires from China through the Wenjuanxing Sample Service, of which 391 were valid. We then conducted multiple regression analysis and employed the bootstrap method for our tests. The results show that victim sensitivity has a significant effect on perceived time pressure, territoriality, and knowledge hiding, and that a chain mediating effect of perceived time pressure and territoriality is established between justice sensitivity and knowledge hiding. Further, territoriality has a positive moderating effect on perceived time pressure and knowledge hiding, while the mediating effect of perceived time pressure on justice sensitivity and knowledge hiding is also moderated by territoriality. Further, the study offers important practical implications in that enterprises should not blindly pursue results by making employees work excessively overtime. Instead, enterprises should have a certain degree of control, offer rationales for overtime work, and give high wages to the employees to compensate for their time, thus making the employees feel the worthiness of their overtime work and reducing the probability of engaging in knowledge hiding behaviors.